Collaborative leadership : developing effective partnerships in communities and schools - Rubin, Hank. (Thousand Oaks, Calif. : Corwin Press, 2002)
Build and maintain successful collaborative relationships in your school-and watch resources for student achievement soar! With this updated bestseller, educators discover how to use collaboration to shape school culture and help their students learn. Visionary Hank Rubin provides a broad overview of collaboration in education and lays the foundation for working with colleagues, establishing strong partnerships, and cooperating with students to achieve goals. Filled with practical examples and the latest research, this resource examines 14 phases of collaboration and helps educa
Includes bibliographical references.
Keywords: Community and school; Interpersonal Relationship; Educational leadership; Cooperation